Loneliness in Psychosis: A Meta-analytical Review - Michalska da Rocha, Beata; Rhodes, Stephen; Vasilopoulou, Eleni; Hutton, Paul (Schizophrenia bulletin, 2018)
Loneliness may be related to psychotic symptoms but a comprehensive synthesis of the literature in this area is lacking. The primary aim of the current study is to provide a systematic review and meta-analysis of the association between loneliness and psychotic symptoms in people with psychosis. A search of electronic databases was conducted (PsychINFO, MEDLINE, EMBASE, and Web of Science). A random effects meta-analysis was used to compute a pooled estimate of the correlation between loneliness and psychotic symptoms. Study and outcome quality were assessed using adapted versions of the Agency for Healthcare Research and Quality (AHRQ) tool and GRADE approach, respectively. Thirteen studies were included, providing data from 15 647 participants. A moderate association between psychosis and loneliness was observed (k = 13, N = 15 647, r = .32, 95% CI 0.20, 0.44; I2 = 97.56%; moderate quality evidence). Whether loneliness was assessed by a single-item or a more comprehensive measure had no moderating effect on the estimate. Results indicate that there is a significant positive relationship between loneliness and psychosis. Further studies are needed to determine the causal status of this relationship, but this robust finding should be considered in clinical practice and treatment provision for those with psychotic disorders.